2018
DOI: 10.22146/jpti.24759
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Abamectin on Anagrus nilaparvatae, An Egg Parasitoid of Nilaparvata lugens

Abstract: Anagrus nilaparvatae (Hymenoptera: Mymaridae) is an egg parasitoid potential for controlling the major pests on rice, the brown planthopper (Nilaparvata lugens [Hemiptera: Delphacidae]). Abamectin is one of insecticides registered for N. lugens. The research was aimed to investigate the impact of contact application of abamectin on the parasitism level of A. nilaparvatae under laboratory conditions. Adults of A. nilaparvatae and the first instars as well as adults of N. lugens were exposed to the residue of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…This is in line with the reports of Ananiev et al (2002) that abamectin is wide spectrum activity. Sasmito et al 2017) reported that abamectin could decrease abundance of BPH parasitoid (Anagrus nilaparvatae). The abamectin was proven to be able to reduce the abundance of arthropods in rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the reports of Ananiev et al (2002) that abamectin is wide spectrum activity. Sasmito et al 2017) reported that abamectin could decrease abundance of BPH parasitoid (Anagrus nilaparvatae). The abamectin was proven to be able to reduce the abundance of arthropods in rice.…”
Section: Discussionmentioning
confidence: 99%
“…It can produce beauvericin, a toxin for insect pests (Rachmawati et al 2018). While abamectin is an insecticide with broad-spectrum activity (Ananiev et al 2002) and often used by farmers in Indonesia to control a brown planthopper (BPH), Nilaparvata lugens but the abamectin reduced the parasitism level and the number of BPH parasitoid (Anagrus nilaparvatae) progeny emerged (Sasmito et al 2017). This study aimed to compare the abundance of arthropods in main and ratoon rice applied with bioinsecticides derived from entomopathogenic fungi and abamectin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to impacting target insects, pesticides greatly affect natural enemies. The direct impact of the application of sublethal concentration of insecticides caused the mortality of Anagrus nilaparvatae, a parasitic wasp of Nilaparvata lugens, by up to 100%, decreased the parasitic rate by 76.03% and the adult emergence by 99.67% (Sasmito et al, 2017). The application of insecticide reduced the parasitic level of A. nilaparvatae through decreasing fecundity and adult longevity (Meilin et al, 2012;Haryati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The highest decrease in the number of species was found in the plot applied with abamectin. Some species of non-target arthropods got sensitive to abamectin applications, namely species of web-building spiders and Carabidae (Prabawati et al 2019), parasitoids (Anagrus nilaparvatae) (Sasmito et al 2017). In this study, the spider species sensitive to high doses of bioinsecticides (3 and 4 L.ha -1 ) were Camaricus formosus, Oxyopes matiensis, while the predatory arthropods included Ischnura senegalensis, Libellula luctuosa, Ortetrum Sabina.…”
Section: Discussionmentioning
confidence: 66%
“…In addition, the abundance of the Hymenoptera parasitoid also decreased significantly when abamectin was applied. Sasmito et al (2017) reported that abamectin could reduce the ability of the brown planthopper parasitoid (Anagrus nilaparvatae) in parasitizing and also reduced the abundance of these parasitoid offspring. The abundance of herbivores started to decrease when applied with bioinsecticides of 2, 3 or 4 L.ha -1 , but at doses of 3 or 4 L.ha -1 the diversity of species of non-target arthropods (predators and parasitoids) began to decrease.…”
Section: Discussionmentioning
confidence: 99%